2007
DOI: 10.1038/cr.2007.48
|View full text |Cite
|
Sign up to set email alerts
|

Fat poetry: a kingdom for PPARγ

Abstract: Adipose tissue is not an inert cell mass contributing only to the storage of fat, but a sophisticated ensemble of cellular components with highly specialized and complex functions. In addition to managing the most important energy reserve of the body, it secretes a multitude of soluble proteins called adipokines, which have beneficial or, alternatively, deleterious effects on the homeostasis of the whole body. The expression of these adipokines is an integrated response to various signals received from many or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
119
0
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(136 citation statements)
references
References 266 publications
(293 reference statements)
1
119
0
13
Order By: Relevance
“…The requirement for PPARγ is not unexpected, as adipogenic differentiation requires PPARγ activity (24). Our conclusions related to the requirement for EMT rest on several observations: adult heart injury induces EMT and induces fat when PPARγ is expressed (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The requirement for PPARγ is not unexpected, as adipogenic differentiation requires PPARγ activity (24). Our conclusions related to the requirement for EMT rest on several observations: adult heart injury induces EMT and induces fat when PPARγ is expressed (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Peroxisome proliferator-activated receptor g (PPARg) is a major regulator of adipogenesis and adipose tissue insulin sensitivity. 27 PPARg protein levels were reduced in chow diet-fed NOX4-deficient mice compared with WT mice. HFD feeding led to a decrease in PPARg expression in both WT and NOX4-deficient mice that diminished the difference between genotypes (P ¼ 0.013 Student's t-test) (Figure 3m).…”
Section: Resultsmentioning
confidence: 99%
“…We found that the Pro12 allele of PPARG2 was significantly associated with elevated adipocyte IR index and nominally associated with increased liver IR. Peroxisome proliferator-activated receptor (PPAR)γ is a nuclear factor regulating transcriptor of various genes, particularly adiposespecific genes involved in adipocyte differentiation, and contributes to regulation of NEFA metabolism by stimulating uptake, storage and oxidation of NEFA in adipocytes [25]. The relevant SNP has been previously shown to be associated with insulin sensitivity [1,26,27].…”
Section: Discussionmentioning
confidence: 99%